2019
DOI: 10.3390/s19194197
|View full text |Cite
|
Sign up to set email alerts
|

Massive Automatic Identification System Sensor Trajectory Data-Based Multi-Layer Linkage Network Dynamics of Maritime Transport along 21st-Century Maritime Silk Road

Abstract: Automatic Identification System (AIS) data could support ship movement analysis, and maritime network construction and dynamic analysis. This study examines the global maritime network dynamics from multi-layers (bulk, container, and tanker) and multidimensional (e.g., point, link, and network) structure perspectives. A spatial-temporal framework is introduced to construct and analyze the global maritime transportation network dynamics by means of big trajectory data. Transport capacity and stability are explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…For example, in [78], the authors found that container ships follow regularly repeating paths, whereas bulk dry carriers and oil tankers move less predictably between ports. To fully consider the spatial relationships between different types of maritime transport networks, rather than aggregating all layers of networks, multi-layer network methods can be applied to study global maritime transport networks [89,92,93]. The efficiency of maritime transportation has a major impact on global economic development, international politics and social and economic exchanges.…”
Section: Large Maritime Graphsmentioning
confidence: 99%
“…For example, in [78], the authors found that container ships follow regularly repeating paths, whereas bulk dry carriers and oil tankers move less predictably between ports. To fully consider the spatial relationships between different types of maritime transport networks, rather than aggregating all layers of networks, multi-layer network methods can be applied to study global maritime transport networks [89,92,93]. The efficiency of maritime transportation has a major impact on global economic development, international politics and social and economic exchanges.…”
Section: Large Maritime Graphsmentioning
confidence: 99%
“…Zhao et al [34] studied the energy interdependence between China and countries along the Belt and Road region and found that they have established an interdependent relationship; it was also observed that China is in a passive position relative to the countries located along the route. Yu et al [35] used a multilevel spatiotemporal dynamics framework to analyze the temporal and spatial dynamics of the global ocean network and found that China, Singapore, South Korea, and other ports in the countries located along the Silk Road have established new shipping relationships; the new connections carry significant traffic flow. However, most of the existing research on shipping relations remains at the level of studying the breadth and intensity of the connections and does not go deeply into the quantitative study of relation types.…”
Section: Traffic Relations and Statusmentioning
confidence: 99%
“…Construction of maritime network using AIS data: (a) Positioning different ships routes by real-time longitude and latitude information; (b) Identifying the ports in routes, and building a maritime network with ports as nodes;(c) Combining WPI and national basic information data to build a maritime network with countries as nodes. Source: Adapted from Yu et al[35].…”
mentioning
confidence: 99%
“…Based on the AIS data of containers, crude oil and bulk in 2014, Mou et al [14] analyzed the spatial distribution pattern of the maritime transport network of Maritime Silk Road and the current situation of regional trade relations, putting forward suggestions for the construction of ports along the Maritime Silk Road and the sustainable development of the economy. Yu et al [15], through the introduction of the time-space framework and the use of a large amount of AIS trajectory data, built and analyzed the dynamics of the global maritime transport network. Besides, they examined the dynamics of the global maritime network from the perspective of multilayer (bulk, container, and tanker) and multi-dimensional (e.g., point, connection, and network) structure.…”
Section: ) Relevant Research On Comprehensive Network Of Container Oil and Bulkmentioning
confidence: 99%